NATIONAL IDENTITY AND MYSTICAL BEAUTY IN WILLIAM BUTLER YEATS’ „CELTIC TWILIGHT” - Tolordava, Natia (International Journal of Innovative Technologies in Social Science, 2022)
The end of 19th century was generally a significant and transitional period, as from the beginning of the 20th, modernism was gradually replacing the Victorian era. However, the prospect of change was even more immediate in Ireland than anywhere else. The Irish hoped to escape from the colonial restrictions imposed by the state, and from the new century they already counted themselves among the free nations. Yeats shared the same spirit, and therefore the awarding of the Nobel Prize in 1923 had a symbolic meaning for him, since Ireland had just gained independence. And the poet used every possible occasion to point it out and replied to congratulatory letters in this way: "I consider myself to have received this award as a representative of Irish literature and not as an independent person. Welcome to the free state.” [Foster 2003, p. 656.]